25-(OH)D Deficiency and the Risk of Minor Amputation in Patients with Diabetes Foot Ulcers: A Chinese Cohort Study - Qian Z; Sun Y; Bai J; Jiang B; Zhao J (International Journal of General Medicine)
Zhikai Qian, Yongyang Sun, Jinyu Bai, Bo Jiang, Jiaju Zhao Department of Orthopedics, The Second Affiliated Hospital of Soochow University, Soochow, 215004, People’s Republic of ChinaCorrespondence: Jiaju Zhao, Department of Orthopedics, The Second Affiliated Hospital of Soochow University, Soochow, 215004, People’s Republic of China, Tel/Fax +86-512-67784127, Email zpj1985@163.comBackground: Diabetic foot amputation represents the severe complication of patients with diabetic foot ulcers (DFU), with worsened clinical outcomes concomitant with 25-hydroxyvitamin D [25-(OH)D] deficiency. This study aimed to investigate the value of 25-(OH)D deficiency and its association with minor lower limb amputation in Chinese patients with DFU in type 2 diabetes mellitus (T2DM).Methods: Ninety-one T2DM patients with DFU undergoing minor amputation (surgical group), 94 T2DM patients without DFU (diabetic control group), and 40 healthy controls were enrolled in the study finally. Serum 25-(OH)D levels were measured by stable isotope dilution-high performance liquid chromatography-tandem mass spectrometry. Patients in the surgical group underwent pathogen detection.Results: The overall incidence of 25-(OH)D deficiency was 73.0%. Amputation group exhibited significantly higher prevalence versus control group (85.7% vs 60.6%, P< 0.001). The levels of serum 25-(OH)D in the minor amputation group were significantly lower than the T2DM group [10.71 (8.2,16.7) vs 18.8 (15.0, 23.9) ng/mL, P< 0.001]. Compared with the control group, amputation group showed lower 25-(OH)D, calcium, albumin and higher WBC, platelet, inflammatory markers (all P< 0.001). Minor amputation subgroups showed that 25-(OH)D deficiency associated with elevated WBC (P=0.002), PLT (P=0.011), D-dimer (P=0.041), HbA1c (P=0.033), SII (P=0.023). While low expression of 25-(OH)D group had higher WBC (P=0.016), D-dimer (P=0.004), SIRI (P=0.042), lower albumin (P=0.009) vs high expression group. ROC analysis confirmed 25-(OH)D as superior amputation predictor (AUC=0.798, 95% CI 0.734– 0.861) compared to inflammatory markers. Multivariate regression identified deficiency as independent amputation risk factor. Polymicrobial infections (26.4%) correlated with lower 25-(OH)D (P=0.003), with Gram-negative (52.4%) and Gram-positive bacteria (47.6%) among bacterial infections.Conclusion: 25-(OH)D deficiency occurs in 85.7% of patients with minor amputation in DFU, and the levels of 25-(OH)D decreased. 25-(OH)D deficiency is a vital risk factor for minor amputation and measures should be taken to prevent 25-(OH)D deficiency in T2DM patients with DFU.Keywords: 25-(OH)D deficiency, diabetic foot ulcers, minor amputation, type 2 diabetes mellitus